2015
DOI: 10.1111/anae.13180
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the optic nerve sheath to assess intracranial pressure changes after ventriculo‐peritoneal shunt surgery in children with hydrocephalus: a prospective observational study

Abstract: SummaryThe optic nerve sheath diameter has been verified by various clinical studies as a non-invasive indicator of intracranial hypertension. The aim of this study was to compare the optic nerve sheath diameter before and immediately after ventriculo-peritoneal shunt surgery in children with hydrocephalus. We analysed transorbital ultrasonographic images recorded after induction of anaesthesia and 30 min after shunt insertion in 34 children, measuring the optic nerve sheath diameters using a linear ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 17 publications
4
16
1
Order By: Relevance
“…Hansen et al found that changes in optic nerve sheath diameter are closely associated with intracranial pressure variations within a limited intracranial pressure interval (20-50 mmHg), and ongoing enlargement of optic nerve sheath diameter on serial ultrasonography has clinical relevance 24 . Several studies of the relationship between optic nerve sheath diameter and intracranial pressure have shown that optic nerve sheath diameter is a useful method for detecting elevated intracranial pressure in children and adults 15,[25][26][27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hansen et al found that changes in optic nerve sheath diameter are closely associated with intracranial pressure variations within a limited intracranial pressure interval (20-50 mmHg), and ongoing enlargement of optic nerve sheath diameter on serial ultrasonography has clinical relevance 24 . Several studies of the relationship between optic nerve sheath diameter and intracranial pressure have shown that optic nerve sheath diameter is a useful method for detecting elevated intracranial pressure in children and adults 15,[25][26][27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…Use of caudal block causes an increase in intracranial pressure in paediatric patients 13 , but the effect of epidural analgesia on intracranial pressure in paediatric patients has not been investigated. Studies of non-invasive methods used for intracranial pressure measurement have demonstrated that optic nerve sheath diameter is correlated with intracranial pressure; optic nerve sheath diameter measurement has high diagnostic accuracy for detection of increased intracranial pressure in children [14][15][16] . This prospective, randomised, double-blinded study aimed to investigate the effects of lumbar epidural bolus and infusion on intracranial pressure using ultrasonographic optic nerve sheath diameter measurements in children.…”
mentioning
confidence: 99%
“…If the changes in either pEEG monitoring or cerebral saturation are unilateral, and the peripheral or somatic NIRS saturation is normal, localized cerebral hypoperfusion should be suspected. Furthermore, cerebral investigation should be pursued, such as a carotid, jugular, and brain ultrasound, TCD, 15 optic nerve sheath measurement, 16,17 and/or computed tomography. On the other hand, if the cerebral saturation reduction is bilateral and symmetrical and the somatic NIRS saturation is also reduced, then a non-cerebral etiology such as cardiogenic shock, hemorrhagic shock, hypoxemia or obstruction to adequate central venous drainage (superior or inferior vena cava) is more likely, as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Serial tracking of acute changes could be useful in a patient at risk for intracranial hypertension secondary to trauma, to monitor the results of treating a patient with IIH, or after ventriculoperitoneal shunt placement. 3…”
Section: Using Onsd Us To Monitor Rapid Changes In Icpmentioning
confidence: 99%
“…2 Other reasons to monitor ICP include the management of pseudotumor cerebri or after ventriculoperitoneal shunt surgery. 3 Unfortunately, current methods of ICP monitoring have significant drawbacks and limitations. The gold standard of ICP monitoring-measurement using an in-Mr Lesky was a medical student, University of Pittsburgh School of Medicine, Pennsylvania, at the time this article was written.…”
mentioning
confidence: 99%